2017
DOI: 10.3390/children4110100
|View full text |Cite
|
Sign up to set email alerts
|

Parent Cardiac Response in the Context of Their Child’s Completion of the Cold Pressor Task: A Pilot Study

Abstract: Parents’ ability to regulate their emotions is essential to providing supportive caregiving behaviours when their child is in pain. Extant research focuses on parent self-reported experience or observable behavioural responses. Physiological responding, such as heart rate (HR) and heart rate variability (HRV), is critical to the experience and regulation of emotions and provides a complementary perspective on parent experience; yet, it is scarcely assessed. This pilot study examined parent (n = 25) cardiac res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…Specifically, research has demonstrated that lower levels of resting HRV are associated with higher levels of pain unpleasantness [3] and reduced inhibition of fear responses [43,72]. Preliminary evidence suggests parental resting HRV relates to altered parental physiological responding when facing their child's pain [14], yet its precise role for parental self-reported distress and pain-control behaviour elicited by facing child's pain remains to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research has demonstrated that lower levels of resting HRV are associated with higher levels of pain unpleasantness [3] and reduced inhibition of fear responses [43,72]. Preliminary evidence suggests parental resting HRV relates to altered parental physiological responding when facing their child's pain [14], yet its precise role for parental self-reported distress and pain-control behaviour elicited by facing child's pain remains to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Trait HRV has been implicated in the inhibition of fear responses (Wendt et al, 2015) and deemed an important factor in regulating emotions in both personal and interpersonal pain contexts (Constantin, McMurtry, et al, 2017; Koenig et al, 2016; Vervoort et al, 2014, 2019), whereas much less is known about how state HRV may relate to threat-oriented states and behaviors. Preliminary work on parent trait HRV demonstrates an association with past experiences with pain (Constantin, Moline, et al, 2017) and pain control behaviors (Vervoort et al, 2019). Initial work also demonstrates that parent state HRV decreases when viewing pictures of children displaying varying levels of facial expressions of pain (Vervoort et al, 2014) and immediately before their child’s completion of the cold pressor task (CPT; Constantin, Moline, et al, 2017).…”
mentioning
confidence: 99%
“…Preliminary work on parent trait HRV demonstrates an association with past experiences with pain (Constantin, Moline, et al, 2017) and pain control behaviors (Vervoort et al, 2019). Initial work also demonstrates that parent state HRV decreases when viewing pictures of children displaying varying levels of facial expressions of pain (Vervoort et al, 2014) and immediately before their child's completion of the cold pressor task (CPT; Constantin, Moline, et al, 2017). Missing from the literature is a foundational understanding of how parent HRV, as a correlate of emotion regulation, relates to parent verbal behaviors and responses that are commonly observed during child acute pain.…”
mentioning
confidence: 99%
“…The time‐domain measure of HRV, RMSSD, reported a mean of 4.08 ( SD , 0.52). These indices were calculated using the same methodology as Constantin et al (2017), whose study included 25 parents of children aged between 7 and 12 years and reported HF‐HRV with a mean of 6.02 ( SD , 0.84) and RMSSD with a mean of 6.72 ( SD , 0.86).…”
Section: Resultsmentioning
confidence: 99%